Corruption and Iraq Banks Performance: Expanding the “Grease or Sand the Wheel” Hypothesis - Altaee, Hatem Hatef Abdulkadhim; Alsalim, Munadhil Abduljabar; Ghani, Naz Hiwa (Zanco Journal of Human Sciences, 2024)
The main goal of the study is to investigate the effect of corruption on the profitability of Iraqi banks during the period 2012–2020. The paper used a sample of nine private banks that account for a considerable proportion of the overall assets of the Iraqi commercial banks. The advanced technique of method of moment quantile regression (MMQREG) is used. To validate the initial results, we use the feasible generalized least squares (FGLS) and panel-corrected standard errors (PCSEs) techniques. Our results support the ‘grease or sand the wheel’ hypothesis of corruption for Iraqi banks. This finding supports the view that the current weak governance structures and the power-sharing political system in the country serve as an ‘escape hatch’ for individuals in power. Furthermore, the findings of the PCSE and FGLS validated the MMQREG results in terms of coefficient sign. Correspondingly, income and inflation are shown to be positive drivers of ROAA. Furthermore, it was demonstrated that Iraqi banks are not getting any benefit from economies of scale regarding financial performance. On the other hand, our results reveal that the ratio of cost income has a statistically significant negative effect on bank profitability, implying that Iraqi private banks are operating below their optimal capacity.